Hearing and Vision Screening Program for newborns in Italy - Bubbico, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The aims of this paper were to present data on the implementation and coverage of simultaneous Universal Neonatal Hearing and Vision Screening programmes and to evaluate the organization and management of these healthcare procedures in Italy. Materials and Methods. Data were collected through a nationwide survey conducted in 2018. All maternity wards active in Italy in 2017 were included. Results. Hearing screening. Overall 427,365 newborns out of 448,386 (95.3%) received the hearing screening test (first level) in 391 out of the 409 maternity hospitals (95.5%), with a national mean referral rate of 3.63% (SD ± 4.58). A statistically significant increase (p<0.034) of newborns sent to audiological examination was found in maternity hospitals with Neonatal Intensive Care Unit (NICU) with “TEOAE only” protocol (9.32% SD ± 7.57), compared to those with “TEOAE/AABR” (3.0% SD ± 3.29). Vision screening. Overall 335,262 newborns out of 448,386 (74.7%) received vision screening (Red Reflex test) for vision impairment in 302 out of 409 maternity hospitals (73.8%), before nursery discharge. The mean referral rate, recorded in only 22 maternity hospitals out of 302 (7.2%), was 0.48% with a rate of lost to follow up of 0.75 %. Conclusions. Our results show that implementation of simultaneous hearing and vision screening increased the coverage of both screening tests and is a new multi-disciplinary approach to sensorineural disability. The use of both ABR and TEOAE tests in the hearing screening decreases the number of newborns sent for audiological evaluation, with a notable reduction of costs. The consideration that ocular problems are two to three times more common in deaf and hearing impaired children than their in hearing peers, confirms the importance of establishing guidelines for simultaneous hearing and vision screening, that favors the formation of a multi-disciplinary team (pediatrician, audiologist, ophthalmologist).